Internalisasi Doktrin Kiai di Pondok Pesantren Baitul Hikmah Haurkuning Tasikmalaya - Puadah, Nurul; Manshur, Fadlil Munawwar; Sumadi, Sumadi (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2019)
The problems examined in this study are: What are the doctrines of the kiai in Baitul Hikmah Haurkuning Islamic Boarding School Tasikmalaya ?; what is the perception of pesantren residents towards the kiai doctrine at Baitul Hikmah Haurkuning Islamic Boarding School Tasikmalaya ?; and how is the internalization of the kiai's doctrine at Baitul Hikmah Haurkuning Islamic Boarding School in Tasikmalaya? The research method used is descriptive analytic method with qualitative type. The data collection techniques that will be used in this study are: observation techniques, interview techniques, documentation techniques. The data analysis techniques in this study are: data reduction, data display, data verification or drawing conclusions. After carrying out research, the authors reach the following conclusions: 1) The doctrine of the kiai in the Baitul Hikmah Islamic Boarding School Haurkuning Tasikmalaya included in the boarding school curriculum. 2) Perceptions of pesantren residents to the kiai doctrine in the Baitul Hikmah Islamic Boarding School in Tasikmalaya, there are positive and negative perceptions, depending on their understanding against the doctrine itself. 3) Internalization of the doctrine of the kiai in the Baitul Hikmah Haurkuning Tasikmalaya boarding school is carried out in the administration of education in the boarding school realized in the learning system in the Baitul Hikmah Haurkuning Tasikmalaya boarding school.